Study on the Cost of Cultivation, Returns, and Benefit-Cost Ratio of Betel Vine Farmers in Different Farm Groups in Bankura District, India - , Sambuddha Mukherjee; , Sanjay Kumar (Archives of Current Research International, 2024)
Agriculture is the backbone of the Indian economy and plays a crucial role in the social and economic fabric of the country. It not only contributes to national income, food security, and employment generation but also fosters cultural unity and economic cohesion within society. This study focuses on betel vine cultivation in the Taldangra Block of Bankura district, West Bengal, where commercial betel cultivation is prevalent. Hence the study area was selected using purposive and convenient sampling methods to ensure representation of the dominant betel cultivation practices. To minimize recall biases, researchers established personal rapports with farmers before conducting surveys and collecting data. The study was conducted during the agricultural year 2023-24, with primary data collected from 120 farmers in seven randomly selected villages. The data collected aimed to assess the cost of establishing and maintaining betel orchards, total cultivation costs, returns, and the benefit-cost ratio for farmers. A semi-structured and pretested schedule, utilizing Participatory Rural Appraisal (PRA) techniques, was employed for data collection and farm economic evaluation. The results revealed that the total cultivation costs for marginal, small, semi-medium, medium, and large farmers were ₹457,943 ; ₹441,850; ₹430,115; ₹425,828 and ₹419,168, respectively. The cost-benefit ratios for these categories of farmers were 2.4, 2.5, 2.44, 2.2, and 2.7, respectively. Large farmers had a higher benefit-cost ratio of 2.7, while semi-medium farmers had a lower ratio of 2.2.